ความสัมพันธ์ระหว่างกระแสเงินสดจากกิจกรรมจัดหาเงินกับผลตอบแทนหลักทรัพย์และผลการดำเนินงานในอนาคตของบริษัทจดทะเบียนในตลาดหลักทรัพย์แห่งประเทศไทย - อภิเดช แววสุวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The purpose of this study is to analyze the association between cash flow from corporate financing activities, future stock returns, and future performances of listed companies in the Stock Exchange of Thailand (SET). The study classifies corporate financing activities into 3 categories (1) net external financing activities (2) debt financing activities and (3) equity financing activities. The sample is selected from listed companies during the year 2000 to 2005. Both descriptive statistic and multiple regression are employed for the data analysis. The data is analyzed for each industry.When data is separately analyzed for each of 8 industries, at 95% confidence interval, the results found that net corporate financing activities are negatively correlated with the future returns of 4 business industries including agro & food Industry, consumer products, industrials and services. The results concerning the relationship between corporate financing activities and future performances found that all three categories of corporate financing activities are negatively correlated with the future performances of 6 industries including agro & food industry, consumer products, property & construction, Industrials, services and information & communication technology.